108k views
1 vote
Inverse of the function h(x)=\dfrac{3}{2}(x-11)h(x)= 2 3 ​ (x−11)h, left parenthesis, x, right parenthesis, equals, start fraction, 3, divided by, 2, end fraction, left parenthesis, x, minus, 11, right parenthesis?

User Sorashi
by
6.4k points

1 Answer

0 votes

Answer:


h^(-1)(x)=(2)/(3)x+11

Explanation:

The given function is


h(x)=(3)/(2)(x-11)

We need to find the inverse of the given function.

Step 1: Substitute h(x)=y.


y=(3)/(2)(x-11)

Step 2: Interchange x and y.


x=(3)/(2)(y-11)

Step 3: Isolate y.


(2)/(3)x=y-11


(2)/(3)x+11=y

Step 4: Interchange sides.


y=(2)/(3)x+11

Step 5: Substitute
y=h^(-1)(x).


h^(-1)(x)=(2)/(3)x+11

Therefore, the inverse of the function is
h^(-1)(x)=(2)/(3)x+11.

User Akhikhl
by
6.5k points